Spectral variations of the output spectrum in a random distributed feedback Raman fiber laser. - Sarmani, Abdul Rahman; Abu Bakar, Muhammad Hafiz; A. Bakar, Ahmad Ashrif; Mahamd Adikan, Faisal Rafiq; Mahdi, Mohd Adzir (Optical Society of America, 2011)
We report an ultra-long Raman laser that implemented a variable pumping scheme in backward and forward configurations. Rayleigh backscattering effects were realized in the 51 km fiber length that functioned as a virtual mirror at one fiber end. With the employment of a fiber Bragg grating that has a peak reflection wavelength at 1553.3 nm, spectral broadening effects were observed. These occurred as the pump power level was diverted more to the forward direction. Owing to this fact, a maximum width of 0.9 nm was measured at 100% forward pumping. The obtained results show that the efficient exploitation of four-wave mixing interactions as well as strong Rayleigh backscattering are beneficial to influence the lasing performances. Both of these nonlinear responses can be adjusted by varying pumping distributions along the fiber longitudinal dimension.